THE EXAMINATION OF STRATEGIES OF AMATEUR AND PROFESSIONAL MUSICIANS’ USE WHILE PRACTICING AND LEARNING MUSIC IN THE INSTRUMENTS - Özlem KILINÇER; Mehtap Aydıner UYGUN (International Journal of Eurasia Social Sciences, 2017)
The purpose of this study was to examine the strategies amateur and professional musicians in Turkey use while practicing and learning music on their instruments. These strategies were attention, repetition, elaboration, articulation-organization and comprehension monitoring strategies. There were a total of 515 musicians, 412 amateurs and 103 professional, in the study group. The group of amateur musicians participating in the study consisted of 139 students studying at four different fine arts high schools in Turkey and 273 students studying at music education departments of four different universities. The group of professional musicians consisted of 103 orchestra artists who were working in four different orchestras in Turkey in 2016. The data was collected through Personal Information Form and Scale for Strategies Used during the Practice and Learning of Instrumental Music. As a result of the study, it was determined that amateur musicians’ attention and articulation-organization levels were higher than professional musicians’ attention and articulation-organization levels. It was also determined that professional musicians’ comprehension monitoring strategy levels were higher than amateur musicians’ comprehension monitoring strategy levels. Based on the study results, it was suggested that researchers can conduct experimental new studies examining amateur and professional musicians’ strategies while they practice and learn in instrumental music.